2015
DOI: 10.4220/sykepleienf.2015.55007
|View full text |Cite
|
Sign up to set email alerts
|

Dokumentasjon og oppfølging av bebuarar med diabetes i sjukeheim

Abstract: Background:The healthcare system in Norway has a goal of basing services on research-based knowledge. Studies indicate that recommended and clinical practice frequently deviate. Little is known about the quality of follow-up of people with diabetes in nursing homes in Norway, but international studies show a great variation in the quality of diabetes care for residents of institutions.Objective: The purpose of this study was to determine whether the procedures for monitoring glycaemic control among nursing-hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…The fact that only 55% of the participants in this study reported familiarity with the diabetes guidelines for older nursing home residents can raise questions about where in the system dissemination of new and relevant knowledge fails, and why. Promoting the implementation of clinical guidelines in Norwegian nursing homes and not at least appropriate use of guidelines can lead to awareness among nursing personnel of the need to take informed decisions [ 34 ], which can enhance patient safety [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that only 55% of the participants in this study reported familiarity with the diabetes guidelines for older nursing home residents can raise questions about where in the system dissemination of new and relevant knowledge fails, and why. Promoting the implementation of clinical guidelines in Norwegian nursing homes and not at least appropriate use of guidelines can lead to awareness among nursing personnel of the need to take informed decisions [ 34 ], which can enhance patient safety [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trinn 1: Innsatsområda blei drøfta på postane. Det var naturleg å ta utgangspunkt i studien frå 2011 (4). Ladegården var ein av sjukeheimane som deltok i denne studien.…”
Section: Evaluering Av Praksisunclassified
“…Gjennomføringa av klinisk audit, som inkluderte ti bebuarar med diabetes, viste klar betring på fleire område, samanlikna med funna i Heimro sin studie frå 2011 (4). Ved tidspunktet for re-audit var diagnosen dokumentert i alle pasientjournalane til bebuarane med diabetes.…”
Section: Drøftingunclassified